2022
DOI: 10.3389/fcell.2022.832803
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Methylation-Regulating Genes Prognostic Signature to Predict the Prognosis and Aid Immunotherapy of Clear Cell Renal Cell Carcinoma

Abstract: Methylation is one of the most extensive modifications of biological macromolecules and affects cell-fate determination, development, aging, and cancer. Several methylation modifications, including 5-methylcytosine and N6-methyladenosine, play an essential role in many cancers. However, little is known about the relationship between methylation and the prognosis of clear cell renal cell carcinoma (ccRCC). Here, we established a methylation-regulating genes prognostic signature (MRGPS) to predict the prognoses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…P value < 0.05 and |log2(FC)| > 1.0 indicated statistically significant results. The expression of NSUN6 and NOP2 has previously been confirmed in ccRCC [ 41 ]. Wu et al reported that both NSUN2 and NOP2 were highly expressed in ccRCC cells and tissues [ 42 ].…”
Section: Methodsmentioning
confidence: 89%
“…P value < 0.05 and |log2(FC)| > 1.0 indicated statistically significant results. The expression of NSUN6 and NOP2 has previously been confirmed in ccRCC [ 41 ]. Wu et al reported that both NSUN2 and NOP2 were highly expressed in ccRCC cells and tissues [ 42 ].…”
Section: Methodsmentioning
confidence: 89%
“…The ability of the model to correctly classify the research event was evaluated by ROC curves and concordance index (C-index). The ROC curves and C-index) were also used to compare the models we built with others ( He et al, 2021 ; Zhang F. et al, 2021 ; Chen et al, 2022 ; Sun et al, 2022 ; Zhang et al, 2022 ). The differences in the predicted survival events and the virtually observed outcomes were compared by calibration plots of the nomogram.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to m 6 A modification, m 5 C RNA methylation is also required for the regulation of the immune microenvironment in diverse cancer types. Increasing evidence has identified multiple m 5 C RNA regulators are abnormally expressed in many cancer tissues and play important roles in modulating immune functions in cancer 474–477 . In triple‐negative BC, NSUN2 has been found to be expressed in monocytes/macrophages and NSUN6, on the other hand, is expressed in Treg cells 478 .…”
Section: Association Of Rna Methylation With Cancer Immunitymentioning
confidence: 99%
“…Increasing evidence has identified multiple m 5 C RNA regulators are abnormally expressed in many cancer tissues and play important roles in modulating immune functions in cancer. 474 , 475 , 476 , 477 In triple‐negative BC, NSUN2 has been found to be expressed in monocytes/macrophages and NSUN6, on the other hand, is expressed in Treg cells. 478 Additionally, NSUN6 expression has been shown to correlate strongly with multiple immune cells, particularly CD4+ T cells, suggesting a broader role in modulating immune responses.…”
Section: Association Of Rna Methylation With Cancer Immunitymentioning
confidence: 99%